1994
DOI: 10.1177/030098589403100602
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Canine Mast Cell Tumors: A Comparison of Three Methods

Abstract: Abstract. In this study, age, sex, recurrence, metastasis, death rate, and histologic patterns were in agreement with those of previous reports on canine mast cell tumors. Histologic grading, mitotic index, chromosome nucleolar organizer regions stained with silver (AgNORs), and anti-proliferating cell nuclear antigen (PCNA) were evaluated as indicators of prognosis. Histologic grading, AgNORs estimated in 100 cells, and PCNAlabeled fraction estimated in five high power fields (HPFs) were significantly differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
162
5
68

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(242 citation statements)
references
References 31 publications
7
162
5
68
Order By: Relevance
“…In this study, the most commonly affected breed was the Boxer, which is consistent with studies in the literature reporting a hereditary predisposition for animals related to the Bulldog, such as Boxers (O' Keefe, 1990;Simoes et al, 1994;Lemarié et al, 1995;Fox, 1998;London and Seguin, 2003;Misdorp, 2004;Costa et al, 2007;Strefezzi et al, 2009;Costa-Casa Grande et al, 2008). Golden Retrievers are also reported to be over-represented (Bostock and Dye, 1973).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In this study, the most commonly affected breed was the Boxer, which is consistent with studies in the literature reporting a hereditary predisposition for animals related to the Bulldog, such as Boxers (O' Keefe, 1990;Simoes et al, 1994;Lemarié et al, 1995;Fox, 1998;London and Seguin, 2003;Misdorp, 2004;Costa et al, 2007;Strefezzi et al, 2009;Costa-Casa Grande et al, 2008). Golden Retrievers are also reported to be over-represented (Bostock and Dye, 1973).…”
Section: Discussionsupporting
confidence: 89%
“…The survival time of dogs with multiple MCTs was not significantly different to dogs with solitary tumors. Multiple tumors were more prevalent in this study than previously reported in the literature (3-14% from Macy, 1985;O'Keefe, 1990;Simoes et al, 1994).…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…This points to the usefulness of cell proliferation studies. PCNA and Ki-67 have been used for many years as markers of cell proliferation, and both constitute established prognostic factors for MCT (Simoes et al 1994, Abadie et al 1999, Bergman et al 2004). However, to the best of our knowledge, this study was the first analysis of MCM-3 expression in canine mast cell tumours.…”
Section: Discussionmentioning
confidence: 99%